2011
DOI: 10.1017/s0317167100011537
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Stroke Rehabilitation for Stroke Survivors Using Home Care

Abstract: Although many advances have been made in stroke prevention and management, stroke continues to be a prevalent and burdensome condition, particularly among older adults 1 . Stroke is the leading cause of adult disability and the third leading cause of death in Canada 2,3 . More than 50,000 Canadians experience a stroke each year and more than 300,000 (1% of the population) live with the ongoing effects 4,5 Following a sentinel stroke, there is a 20% chance of having another stroke within two years 6 . The costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(139 citation statements)
references
References 83 publications
2
136
0
1
Order By: Relevance
“…At the same, though, it has been well-reported that older adults who experience a stroke often live with long-term functional impairments. 29,30 Although we cannot speculate based on our data, others have demonstrated ongoing unmet needs for supportive home care services for stroke survivors. 31 We found that the drivers of health care costs varied by the number of comorbid conditions.…”
Section: Resultsmentioning
confidence: 74%
“…At the same, though, it has been well-reported that older adults who experience a stroke often live with long-term functional impairments. 29,30 Although we cannot speculate based on our data, others have demonstrated ongoing unmet needs for supportive home care services for stroke survivors. 31 We found that the drivers of health care costs varied by the number of comorbid conditions.…”
Section: Resultsmentioning
confidence: 74%
“…Of interest, removing the only study 41 that did not involve face-to-face contact resulted in a near significant effect, suggesting that the act of leaving the house and interacting in-person with others may need to be an active ingredient of a social participation intervention. It is important to note that participants only received usual care (and not an attention control) in four 25,31,33,35 out of five studies that showed that support service was more beneficial, and thus, it is not possible to disentangle the effects of attention versus support.…”
Section: Discussionmentioning
confidence: 99%
“…One study each reported that no adverse events 25 and no serious adverse events occurred. 37 Seventeen studies [22][23][24]26,27,[29][30][31][32][33][34][35][36]39,[43][44][45] , including ten with exercise components, did not state whether any adverse events occurred or not.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…In 12 studies patients were included immediately after discharge home from hospital, in 1 trial patients were included ≥ 18 months post-stroke (33) and in another trial patients were included after discharge from a rehabilitation centre (35). the period between stroke occurrence and discharge was described by only 3 out of 14 studies (29,35,37), varying from a mean of 45 days (37) to 2.5 years (33).…”
Section: Methodsmentioning
confidence: 99%
“…the assessments were performed at 1 month (38) or 5-6 months after discharge home (29). the second type of intervention (assessment combined with follow-up care) could be subdivided into assessment with either subsequent follow-up visits (n = 5) (25,26,28,33,34) or assessment with subsequent rehabilitation (n = 3) (30-32). the 5 assessments with follow-up visits were aimed at coping with the consequences of stroke (28) and improving the quality of life (33,34).…”
Section: Description Of Interventionmentioning
confidence: 99%